2014
DOI: 10.1002/jca.21340
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining pbsc mobilization efficiency and nonmobilization following ICE with or without rituximab (R‐ICE) salvage therapy for refractory or relapsed lymphoma prior to autologous transplantation

Abstract: ICE/R-ICE (ifosfamide, carboplatin, and etoposide without or with rituximab) chemotherapy followed by autologous stem cell transplantation is an established regimen in refractory/relapsed lymphoma. Few studies have addressed which factors are important in determining peripheral blood stem cell (PBSC) mobilization efficiency or nonmobilization following ICE/R-ICE. Between 2004 and 2013, 88 patients with refractory/relapsed lymphoma who received ICE/R-ICE salvage-chemotherapy prior to granulocyte colony stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Failure to harvest sufficient CD34 þ cells by apheresis occurred in only one 131 I-MIBG-and two chemotherapy-only-treated patients. Of interest, our findings indicate that BM tumor infiltration at diagnosis did impair the mobilization of CD34 þ cells, as described for other tumors (20), even though apheresis only started after clearing of initial BM disease. Concerning the timing of apheresis, there are different approaches: harvesting is performed after two induction chemotherapy courses in North America, as the Children's Oncology group previously showed that this was safe and feasible (21), whereas the consensus in Europe is still to harvest stem cells after the BM is cleared from tumor cells or post induction therapy.…”
Section: Functional and Phenotypic Testing Of Cd34 þ Cellssupporting
confidence: 73%
“…Failure to harvest sufficient CD34 þ cells by apheresis occurred in only one 131 I-MIBG-and two chemotherapy-only-treated patients. Of interest, our findings indicate that BM tumor infiltration at diagnosis did impair the mobilization of CD34 þ cells, as described for other tumors (20), even though apheresis only started after clearing of initial BM disease. Concerning the timing of apheresis, there are different approaches: harvesting is performed after two induction chemotherapy courses in North America, as the Children's Oncology group previously showed that this was safe and feasible (21), whereas the consensus in Europe is still to harvest stem cells after the BM is cleared from tumor cells or post induction therapy.…”
Section: Functional and Phenotypic Testing Of Cd34 þ Cellssupporting
confidence: 73%
“…Several studies carried out to investigate this question showed that the diagnosis of lymphoma, [14][15][16][17][18][19] thrombocytopenia, 14,[20][21][22][23] older age [18][19][20][21][23][24][25] and polytreatment 14,16,19,25,26 , among other factors, emerged as the main potential factors for the prediction of poor recruitment of hematopoietic stem cells.…”
Section: Predictive Factors Of Poor Mobilizationmentioning
confidence: 99%
“…In the present study, the overall mobilization failure rate was 35.2% (45 of 128 patients), the failure rate of MM patients was 26.4% (14 of 53 patients) and that of lymphoma patients was 41% (31 of 75 patients). The mobilization failure rate appeared to be relatively higher than previously reported rates of 5-30% (8,18,19,(21)(22)(23)(24)(25)(26). The reasons for this discrepancy are unknown; however, some invariable or variable factors might have played a role, such as mobilization timing, mobilization schemes, and various parameters set by the separator.…”
Section: Discussionmentioning
confidence: 55%
“…The combined success rate of CTX, CHOP and MINE therapeutic schemes was 68.4%, while that of HyperCVAD scheme plans A or B was only 27.8%, suggesting that HyperCVAD might not be a suitable treatment option for patients with lymphoma. Other studies recommended various schemes with a success rate >70%, which included high-dose CTX, intermediate dose cytarabine, cytarabine combined with etoposide, ESHAP/DSHAP and ICE/RICE (8,(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%